Child Sexual Abuse (CSA) Using Hypnosis - ika meilia, putri dianita; Susanto, Mardi (Jurnal Forensik dan Medikolegal Indonesia, 2023)
Child sexual abuse (CSA) is a global problem and a serious public health issue. Perpetrators often resort to threats and force to incapacitate their victims, including using hypnosis. The use of hypnosis increases the level of difficulty of clinical forensic examination by presenting a diagnostic issue and complicating the formulation of forensic medical expert opinions. This evidence-based case report (EBCR) aims at assessing the available evidence concerning the forensic examination and diagnosis of hypnosis-facilitated CSA. A comprehensive computer-based literature search was performed using several keywords related to the clinical question. The search yielded seven relevant articles. The articles were appraised using general critical appraisal questions from the Centre for Evidence-Based Medicine, University of Oxford. All articles suggest that there might be a place for hypnosis in a criminal investigation (‘forensic hypnosis’). The evidence on the correct application of forensic hypnosis and its benefits are, however, still inconclusive and conflicting. In cases of suspected sexual assault using hypnosis, forensic hypnosis could potentially help memory recall of the victim and aid forward-thinking in drawing a clear and unambiguous conclusion for the forensic medical expert opinion.